Experimental Science Skills of 9th-Grade Students Through Inquiry-Based Learning - Thitisuda Phimthong; Prasart Nuangchalerm; Jutatip Thumsiriwat; Jiří Dostál; Wee Wongtiankul (Journal of Philology and Educational Sciences)
The research aimed to enhance the experimental science skills of 9th grade students by implementing inquiry-based learning management. Specifically, the goal is for students to achieve a passing score of at least 70% of the total points on assessments. The study involved 20 of 9th grade students from Anukulnaree School, located in Kalasin province, Thailand. The action research focused on the development of students' skills in experimental science, particularly through an inquiry-based approach to learning about the separation of substances. An inquiry-based learning management strategy effectively improved the students' experimental science skills. The research instruments were inquiry-based lesson plan, and experimental science skills test. Each cycle was measured by post-test design. Descriptive statistics were employed for data analysis.  The results revealed that 75% of the students met the established criterion of achieving a passing score of 70%. This suggests that the inquiry-based approach was effective in helping students meet the established educational standards.